Analisis Strategi Bauran Pemasaran pada Firdaus Farm - Apdan Pebriana; Dudung Dudung; Agus Hendar; Yaya Sunarya; D Yadi Heryadi (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
This study aims to analyze the implementation of the 4P marketing mix strategy (Product, Price, Place, Promotion) at Firdaus Farm, a tilapia farming business in Tasikmalaya, and its effectiveness in enhancing the business's competitiveness and profitability. The method used is qualitative descriptive with a case study through observations, interviews, and direct documentation at the business location. The research findings indicate that the product strategy, which emphasizes tilapia quality—such as freshness, uniform size, clean packaging, and quality certification—constitutes the primary factor in attracting consumer interest. The flexible and competitive pricing strategy, adjusted according to market conditions and consumer purchasing power, along with bonuses for loyal customers, proved to increase customer loyalty and sales. Product distribution is carried out through traditional channels and has begun utilizing digital platforms to expand market reach, with the strategic location of the business supporting distribution efficiency. Promotion, still mainly traditional, is starting to develop into digital promotion through social media, which effectively increases product visibility and appeal. This study concludes that the consistent and adaptive application of the 4P marketing mix can enhance Firdaus Farm’s competitiveness in the tilapia market. It is recommended that business practitioners continue to develop product innovations, evaluate pricing, expand digital distribution, and optimize digital promotion in order to face increasingly intense market competition.